Analisis Bibliometrik Penerapan Educational Policy Implementation terhadap Merdeka Belajar – Kampus Merdeka - Muhammad Rifqi Aminulloh; Sri Apridayani; Cecep Wahyu Hoerudin (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This paper is a review of previous research on the issue of MKBKM, which is currently being discussed. An innovation that brings extraordinary changes but has very tough challenges. The purpose of this study is to reach a conclusion on the level of research on this issue that has been explored.. Thus, further developments can be directed according to existing needs. Departing from public perception through social media on Twitter regarding this matter. Then a systematic analysis was carried out using bibliometric techniques on 359 Scopus-indexed documents using Biblioshiny and VOS Viewer software. After that, it is applied to policy implementation theory, namely educational policy implementation with four dimensions: smart policy design, inclusive stakeholder engagement, conducive context, and coherent implementation strategy. Using descriptive quantitative methods to generate data that is well-informed and clearly based, we discovered that research on this topic has been conducted since 1977 and has been dominated by authors from the United States until now. The weighting of the discussion focuses on student, study, and system problems. Meanwhile, the policy implementation theory has not been fully implemented and must continue to be developed, especially in each of the existing dimensional elementsKeywords: Independent Learning, Policy, Bibliometric.